Pengaruh Desain Produk terhadap Keputusan Pembelian Produk Elektronik - Eliya Putri Aprilia; Didit Darmawan (Master Manajemen, 2025)
This literature study examines the influence of product design on purchasing decisions for electronic products. Product design is one of several important aspects that manufacturers need to pay attention to when making an item, because product design plays a role in building the reputation or identity of an item, which can be a characteristic of the item and a differentiator from similar items owned by competitors. Product design includes function and form. Design related to form focuses on the planning and appearance of an item, while design related to function focuses on how the item can be used by consumers. In this study, the literature review method was applied by analyzing various relevant scientific sources. The results of the study revealed that product design has a significant influence on consumer purchasing decisions. The main purpose of this literature study is to analyze and synthesize previous research findings on the influence of product design on electronic purchasing decisions and identify factors that influence product design on electronic product purchasing decisions.